The Health of Homeless People in Nottingham: an Exploratory Study - Crocombe, Sophia (2008)
This study sought to explore the perspectives of homeless people in Nottingham concerning health and homelessness. Homeless people are known to suffer from a host of health complaints, yet have great difficulty accessing healthcare. Whilst there has been research into health needs of homeless people, there is limited in-depth research which has explored the health needs and perceptions of healthcare provision from a user's perspective, in relation to specific services in one particular area.